Protective Effects of Betanin against Oxidative Stress in a Peripheral Artery Vasospasm Model in Rat - Kevser Tural; Ozkan Ozden; Zeynep Bilgi; Oğuz Merhan; Celal Sahin Ermutlu; Ayşen Aksoyek (Journal of Investigative Surgery, 2021)
Objective: The aim of this study is to determine protective/modulatory effects of betanin in a femoral artery vasospasm model in rats. Materials and Methods: Sprague-Dawley rats were divided into three groups. Group 1: sham (n = 7), group 2: vasospasm model only (n = 7), group 3: postoperative betanin treatment in the vasospasm model (n = 7). 100 mg/kg betanin was administered orally to group 3 for 7 days, postoperatively. Peripheral blood malondialdehyde (MDA) and nitric oxide (NO) levels were measured for the quantification of oxidative stress, lumen diameter and wall thickness of femoral artery segments were determined to assess vasodilator effects of betanin. Results: Femoral artery vasospasm formation significantly increased both MDA (13.54 ± 3.09 mmol/mL) and NO levels (0.61 ± 0.06 µmol/mL) relative to the sham (9.07 ± 1.09 and 0.48 ± 0.1, respectively). Upon betanin administration, both MDA and NO approached baseline levels (9.95 ± 0.92 and 0.5 ± 0.06, respectively). Pathological examination of lumen diameter and wall thickness of the femoral arteries also revealed that betanin administration resulted in significant increase in lumen diameter when compared to vasospasm group (614.15 ± 245.77 versus 117.40 ± 46.19 µm) and decrease in wall thickness (64.68 ± 14.13 versus 96.73 ± 9.20 µm). Conclusion: Betanin was shown to have protective effect against oxidative stress in a peripheral artery vasospasm model in rats. It may also have a role in mitigating maladaptive changes in arterial structure, as shown in pathological examination.